Reinforcement Knowledge for Ulama in Padang City to Anticipate Hoax about Covid-19 Vaccination - Rahmawati Darussyamsu; Elsa Yuniarti; Ardi Ardi; Ganda Hijrah Selaras (Pelita Eksakta, 2021)
Padang City is the epicenter of the spread of Covid-19 in West Sumatra. The government has issued an Emergency Use Authorization (EUA) for the Covid-19 vaccine, but scholars in the city of Padang are still unsure about vaccination. Therefore, further efforts are needed to provide the right understanding to Padang city clerics about the importance of vaccination, along with its safety and halal. One of the efforts is through the implementation of this community service. This activity has conducted in June 2021, and was attended by 28 participants from 11 sub-district clerics in the city of Padang. The results of the evaluation of the activities show that there has been an increase in the knowledge of scholars about Covid-19 vaccination. In conclusion, this activity has been effectively carried out and can expand the vaccination program in order to break the chain of spread of Covid-19 and achieve herd immunity.